Does tamoxifen have a therapeutic role outside of breast cancer? A systematic review of the evidence. (June 2020) - Clifford, R.E.; Bowden, D.; Blower, E.; Kirwan, C.C.; Vimalachandran, D.
Abstract: Introduction: Tamoxifen is a widely used hormonal based therapy for breast cancer in the adjuvant and metastatic setting, prolonging overall and recurrence-free survival. There has been increasing interest in the potential for novel "off-target" effects of tamoxifen and its metabolite N-desmethyltamoxifen across a number of cancer types. We aim to review the current literature regarding the potential use of tamoxifen in other primary malignancies. Method: A qualitative systematic review was performed according to the PRISMA guidelines using pre-set search criteria across the PubMed, Cochrane and Scopus databases from 1985 to 2019. Additional results were generated from included papers references. Results: A total of 324 papers were identified, of which 47 were included; a further 29 articles were obtained from additional referencing to give a total of 76 articles. Clinical trials have demonstrated benefits with the use of tamoxifen in isolation and combination, specifically in patients with advanced non-resectable malignancy, however results are not consistent across the literature. In vivo data consistently suggests that off target effects of tamoxifen are mediated through the ceramide pathway or through inhibition of protein kinase C (PKC). Conclusions: With increased focus upon the potential of repurposing drugs, tamoxifen may be a candidate for repurposing in the wider cancer setting. There is evidence to suggest that the ceramide or PKC pathway could act as a therapeutic target for tamoxifen or alternative chemotherapeutics and merits further investigation.